Budget multiplier calculation of Mongolia: TV-SVAR model (Mongolian Journal of Economic Review, 2024)
This study aims to assess Mongolia's budget multiplier using the time-varying SVAR (TV-SVAR) model. Notably, it is the first study in Mongolia utilizing the TV-SVAR model to analyze the budget's effects within the economic framework. The research is of significant importance as it contributes to an understanding of the multifaceted impact of fiscal policies on economic dynamics, serving as a pivotal parameter in economic models and facilitating comprehensive policy analyses. Leveraging quantitative data from 2000 to 2020, the research computes the multiplier effects of various components of budget expenditures, encompassing total outlays, wages, investments, transfers, subsidies, and tax policies, on economic growth. The findings reveal a one-year cumulative multiplier of -0.6 for public expenditure and -0.4 for tax revenue, indicating discernible impacts on economic expansion. Specifically, the wage expenditure policy manifests a relatively robust influence on the economy, while transfer and subsidy policies exhibit comparatively weaker effects. Additionally, the study identifies temporal patterns in the budget multiplier's impact, noting an initial increase within the first four months followed by a gradual decline over the subsequent eight months. Since 2010, there has been a consistent escalation in the absolute value of the budget multiplier, signifying an augmenting influence of fiscal policies on the economic landscape over time.Монгол Улсын төсвийн үржүүлэгчийн тооцоо: TV-SVAR загварЭнэхүү судалгааны ажлаар Монгол Улсын төсвийн үржүүлэгчийг хугацааны туршид хувьсах SVAR загвар буюу TV-SVAR загвар ашиглан үнэлэхийг зорилоо. Тус судалгаа нь (i) Эдийн засгийн уналтын сөрөг нөлөөг сааруулахын тулд сангийн, төсвийн, мөнгөний бодлогыг эрчимтэй хэрэгжүүлж буй өнөө үед хийгдэж буй, (ii) Монгол Улсад TV SVAR загвар ашиглан төсвийн нөлөөг судалсан анхны судалгаа болсон, (iii) Эдийн засгийн бүтцийн загваруудад хувьсах параметр болгон ашиглаж (input), бодлогын шинжилгээ хийх боломжтойгоороо өндөр ач холбогдолтой, онцлог юм. Төсвийн нийт зардал, цалин, хөрөнгө оруулалт, шилжүүлэг болон татаас, татварын бодлогын эдийн засгийн өсөлтөд үзүүлж буй нөлөө үржүүлэгчийг тооцохдоо 2000-2020 оны улирлын тоон өгөгдлийг ашигласан. Ингэхэд нэг жилийн хуримтлагдсан үржүүлэгч төсвийн зардлын хувьд -0.6, татварын орлогын хувьд -0.4 байв. Түүнчлэн цалингийн зардлын бодлого эдийн засагт харьцангуй хүчтэй нөлөөлж байгаа бол шилжүүлэг болон татаасын бодлогын нөлөө сул байна. Төсвийн үржүүлэгчийн нөлөө эхний 4 сар өсөж, сүүлийн 8 сар тогтвортой буурах хандлагатай байсан бөгөөд 2010 оноос хойш төсвийн үржүүлэгчийн абсолют утга тогтвортой өсжээ. Өөрөөр хэлбэл, төсвийн бодлогын эдийн засаг дахь нөлөө хугацааны туршид нэмэгдсээр ирсэн байна.Түлхүүр үг:Төсвийн болон сангийн бодлого, төсвийн үржүүлэгч, TV-SVAR загварJEL ангилал: E62, C11, C40